Filsafat Francis Bacon Dalam Konteks Pendidikan Seni - Abadi, Mourent Aulia (Journal of Educational Research and Humaniora (JERH), 2024)
Francis Bacon, as the father of the modern scientific method, emphasized the importance of experience, experimentation, and observation in the acquisition of knowledge. His empirical philosophy, outlined in Novum Organum, has significant relevance in the context of arts education. This study aims to explore how Bacon's principles particularly those related to experimentation, observation, and the elimination of biases can be applied in arts education to enrich the teaching and learning process. The research employs a qualitative approach with descriptive analysis of Bacon's works and literature related to arts education. The findings suggest that arts education based on direct experience and experimentation allows students to develop practical skills, as well as critical and innovative thinking. This approach encourages students to view art as a continuous process, where exploration and new discoveries are always possible, in line with Bacon's view that knowledge is an endless journey. Therefore, Bacon's philosophy provides a strong foundation for creating a more dynamic, open, and creativity-focused approach to arts education.